Church of England and British politics since 1900 - Rodger, Tom; Williamson, Philip, 1953-; Grimley, Matthew (Studies in modern British religious history, 2020)
Bringing together researchers in modern British religious, political, intellectual and social history, this volume considers the persistence of the Church's public significance, despite its falling membership.